Promoting Malaysia’s Cultural Heritage Sites Through Plastic Label Wrapped on the Material Bottle - Jasni Adie, Yasmeen Arnie Jr; Kamaruddin, Norfadilah (Research in Management of Technology and Business, 2024)
Cultural heritage tourism is a great way to attract visitors who are interested in exploring the culture and history of a place. However, many valuable cultural heritage sites in Malaysia are at risk due to a lack of awareness of their historical and architectural significance and the increasing development and urbanization of the country. This can lead to the destruction or neglect of these sites, which can harm tourism and the local community. Therefore, governments, organizations, and individuals need to recognize the value of cultural heritage and take steps to preserve and promote it to tourists. Thus, this study focuses on heritage sites in Malaysia that can utilize their cultural heritage to offer innovative products and alternatives to tourists. By examining the digital illustrations and evaluating the visual impact of plastic label wraps on mineral bottles in conveying Malaysia's cultural heritage, the data collection method used in this research is qualitative, which involves in-depth interviews with three graphic designers to gather information on suitable digital illustrations that can represent these places effectively. The findings can be used to create potential products for tourism and can be applied effectively and efficiently in art and design for educational and innovative purposes.